Tensile strength study of mensiang (scirpuss grossus) fibre composites with unsaturated polyester resin matrix - Hakiim, Evan; Nurdin, Hendri; Abadi, Zainal; Zhuang, Wei-Ting (Journal of Engineering Researcher and Lecturer, 2025)
The mensiang (scirpuss grossus) is a plant that grows on moist and watery land. Mensiang plants are commonly used by the society to produce mats or bags that have a strong and durable texture. This mensiang plant has fibres that can be used as reinforcement in polymer composites as a substitute for synthetic fibres. In composite manufacturing, one of the important factors in determining strength is the fraction between fibre and matrix. This study was conducted to determine the effect of different volume fractions of composites on the tensile strength of mensiang fibre reinforcement. Extraction of fibre from the stem of the mensiang plant was done manually by combing, so that the fibre was obtained. The fibres were then naturally dried by the sun for 2-3 days. The composite manufacturing process was carried out by using the hand lay-up method. Specimens and tensile testing procedures refer to the ASTM D638 standard. Several specimens were made by varying the fibre and matrix fractions. The test results showed that the 12.5% fibre volume fraction had the highest tensile strength. In this study there was no chemical treatment on the fibres before the lamination process, thus, this can be suggested for future researchers to study on the effect of chemical treatment on mensiang fibres on fibre bonding with the matrix.